2020
DOI: 10.1080/20008198.2020.1723857
|View full text |Cite
|
Sign up to set email alerts
|

Translational studies of estradiol and progesterone in fear and PTSD

Abstract: Translational models of fear have greatly informed our understanding of PTSD and its underlying fear circuitry. One of the most replicated findings in the field is the two-fold higher PTSD incidence in females compared to males. While sociocultural factors play a role, the most robust biological influencers to date are gonadal hormones, such as estradiol and progesterone, which fluctuate across the menstrual cycle. Among studies that account for these hormones, most do so in isolation or collect both and only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 58 publications
1
15
0
Order By: Relevance
“…They found that women with PTSD had a deficit in the synthesis of those metabolites, suggesting that lower amounts of progesterone metabolites and not high progesterone per se, explain the findings related to poor extinction retention in PTSD [62]. For a comprehensive summary of studies on estradiol and progesterone in fear and PTSD, please refer to recent reviews [16,63]. In summary, although there has been limited focus on the role of progesterone and testosterone in fear memory processes compared to estradiol research, available evidence points to lower levels of estradiol and progesterone metabolites in the pathogenesis of PTSD.…”
Section: Sex Differences In Neuroendocrine Axismentioning
confidence: 99%
“…They found that women with PTSD had a deficit in the synthesis of those metabolites, suggesting that lower amounts of progesterone metabolites and not high progesterone per se, explain the findings related to poor extinction retention in PTSD [62]. For a comprehensive summary of studies on estradiol and progesterone in fear and PTSD, please refer to recent reviews [16,63]. In summary, although there has been limited focus on the role of progesterone and testosterone in fear memory processes compared to estradiol research, available evidence points to lower levels of estradiol and progesterone metabolites in the pathogenesis of PTSD.…”
Section: Sex Differences In Neuroendocrine Axismentioning
confidence: 99%
“…This technology could generalize beyond the HPA axis. Sex hormones such as estrogen, progesterone, and testosterone all affect learning processes (32,33,4547) and are broadly implicated in psychiatrically relevant functions (6,48,50). Systemic administration of these hormones in animal studies relies on subcutaneous or intraperitoneal injections, which can be stressful and interfere with the sex hormone effects being investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to testosterone, plasma levels of estradiol were not affected by trauma. It remains to be established whether estradiol plays a role in PTSD symptomatology or whether the progesterone/estradiol ratio may be essential for understating sex-dependent differences in fear and PTSD ( Seligowski et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%